Substituição da gordura animal por óleos vegetais reestruturados em hambúrgueres: impactos nutricionais, sensoriais e tecnológicos - Heck, Rosane Teresinha (2021)
Due to the high content of saturated fatty acids, the excessive consumption of meat products can increase the risk of chronic diseases. Thus, to confer healthier characteristics to meat products, this study aimed to improve their lipid profile. Oils with high levels of omega-3 fatty acids were applied in microencapsulated and hydrogelified form as animal fat substitutes in burgers. In the first part of the study the oxidative stability of rosemary-enriched chia oil was evaluated by ultrasound-assisted extraction (UAE) and conventional maceration (CME). In this step it was possible to observe a high concentration of bioactive compounds present in the macerated oils, both by UAE and CME. Then, the chia oil was microencapsulated and used to replace 50% of fat in burgers. The results obtained by directly incorporating rosemary into chia oil by UAE prior to microencapsulation showed that this is a viable alternative to reduce lipid oxidation. The reduction of lipid oxidation in microcapsules made it possible to replace animal fat in burgers with oils rich in n-3 PUFAs, without compromising their oxidative and sensory quality. In the second step, burgers (20 % pork back fat) were prepared with the replacement of 0, 20, 40, 60, 80 and 100 % pork back fat by hydrogelified emulsion (HE) of chia and flaxseed oils (50:50). The substitution of pork back fat with HE did not affect the technological properties of the burgers. The sensory profile showed that it is possible to replace up to 60 % of fat with HE produced in this study. However, improvements in the oxidative stability of HE from chia and flaxseed oils were necessary. Thus, in the third step, HE was enriched at concentrations of 6, 8 and 10 % with an aqueous jabuticaba peel extract (JPE) obtained by microwave extraction by hydrodiffusion and gravity (MHG). The HEenriched with JPE was applied to replace 60 % of animal fat content of the burgers. The addition of 10 % JPE in HE was effective in maintaining lipid oxidation similar to the control until the 60th day of storage. Furthermore, incorporation of JPE into HE reduced sensory defects caused by lipid reformulation. Seeking improvements through the incorporation of natural antioxidants, in the fourth step of this work, residues of yerba mate bark extracts (BMBE) were tested for application in HE and subsequent lipid replacement in burgers. The sensory quality of the burgers was not affected by HE addition of chia oil enriched with BMBE. Furthermore, the addition of BMBE to HE partially reduced the increase in lipid oxidation caused by the increase in PUFA / SFA ratio. Thus, in the present study, new strategies and consistent technological solutions were successfully developed at the industrial level for reducing saturated fat in burgers, resulting in healthier products with high sensory quality.